2011
DOI: 10.1371/journal.pone.0018050
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Trophies Triggers Male Generosity

Abstract: BackgroundCooperation is indispensable in human societies, and much progress has been made towards understanding human pro-social decisions. Formal incentives, such as punishment, are suggested as potential effective approaches despite the fact that punishment can crowd out intrinsic motives for cooperation and detrimentally impact efficiency. At the same time, evolutionary biologists have long recognized that cooperation, especially food sharing, is typically efficiently organized in groups living on wild foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This may suggest that women are more concerned than men about standing out or being judged as image motivated. This fear may relate to women's reluctance to engage in competition (Gneezy et al 2003, Gneezy and Rustichini 2004, Niederle and Vesterlund 2007, Pan and Houser 2011, Kanthak and Woon 2012. Hence, women behave as wallflowers (choosing middle actions) in order to opt-out of the status competition that may be introduced when actions are publicly recognized.…”
Section: Resultsmentioning
confidence: 99%
“…This may suggest that women are more concerned than men about standing out or being judged as image motivated. This fear may relate to women's reluctance to engage in competition (Gneezy et al 2003, Gneezy and Rustichini 2004, Niederle and Vesterlund 2007, Pan and Houser 2011, Kanthak and Woon 2012. Hence, women behave as wallflowers (choosing middle actions) in order to opt-out of the status competition that may be introduced when actions are publicly recognized.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, symbols may incite individuals to outperform others in order to obtain a trophy or to avoid the stigmatization of a negative symbol (e.g. Kosfeld and Neckermann, 2011;Pan and Houser, 2011). On the other hand, previous studies have shown that small monetary but also non monetary rewards such as gold stars, candies or thank-you gestures may crowd-out intrinsic motivation (Deci, 1975;Harackiewicz, 1979;Gneezy and Rustichini, 2000;Cameron et al 2001;Frey and Jegen, 2001;Shalley et al, 2004).…”
Section: H1: Even Under Flat Wages Individuals Exert Positive Levelsmentioning
confidence: 99%
“…Eckel et al 2010); or it is conferred at the end of a play to top contributors as a form of incentive to stimulate competition and promote cooperation (e.g. Pan and Houser 2011). Other early studies explored more broadly the implications of social status, for instance, in markets (e.g.…”
Section: Related Literaturementioning
confidence: 99%